PENERAPAN KUALITAS DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN RUMAH OLEH KONSUMEN PADA PT PUTERA KARYASINDO PRAKARSA BATAM - Rony Prasetyo; Anggia Arista (Universitas Putera Batam, 2018)
The focus of this study is to determine whether the quality of products, product prices can influence the decision to purchase the home either partially or simultaneously by consumers in PT. Putera Karyasindo Prakarsa - Batam. the sample to be used in this study is as many as 98 respondents. This study suspects Partially Product Quality variables positively and significantly affect consumer purchasing decisions in PT. Putera Karyasindo Prakarsa with t count value 4,084 and significance 0.000. Partially Product Price variable positively and significantly influence to Consumer Purchase Decision in PT. Putera Karyasindo Prakarsa with t value 4,367 and significance 0,000. Simultaneously variable Product Quality and Product Price influence together to Purchasing Decision of consumer in PT. Putera Karyasindo Prakarsa with F value count 73,504 with significance level 0.000. The result of detrmination coefficient (R2) or the amount of solution that can be given the variable of quality and price (independent variable) to the problem ie the decision of home purchase by consumer (Dependent variable) equal to 0,607 or 60,7% while the rest 39,3% investigated in this study.